PALEOCLIMATE AND PALEOENVIRONMENT IN NORTH-WESTERN ITALY (SOUTHERN ALPS) DURING THE LAST GLACIAL STAGE: THE SMALL-MAMMAL RECORD FROM THE BUCO DEL FRATE CAVE (PREVALLE – BRESCIA) - Fabio Bona; MARCO BAIONI; ELISABETTA CILLI (Rivista Italiana di Paleontologia e Stratigrafia, 2023)
The palaeoclimatic and palaeoenvironmental data obtained by the study of the Buco del Frate cave small-mammals indicate that, around 40,000 years ago (MIS3), the eastern part of the province of Brescia, immediately to the west of Lake Garda, was characterised by the presence of open taiga environment and watercourses crossing the plain facing the cave.